Expressing Confidence in Models and in Model Transformation Elements. - Burgueño-Caballero, Lola; Bertoa, Manuel F.; Moreno, Nathalie; Vallecillo-Moreno, Antonio Jesús (My University, 2018)
The expression and management of uncertainty, both in the information and in the operations that manipulate it, is a critical issue in those systems that work with physical environments. Measurement uncertainty can be due to several factors, such as unreliable data sources, tolerance in the measurements, or the inability to determine if a certain event has actually happened or not. In particular, this contribution focuses on the expression of one kind of uncertainty, namely the confidence on the model elements, i.e., the degree of belief that we have on their occurrence, and on how such an uncertainty can be managed and propagated through model transformations, whose rules can also be subject to uncertainty.
Keywords: Modelos; Incertidumbre; Uncertainty; Confidence; Models; Model transformations